Peran Guru Bimbingan Konseling Dalam Meningkatkan Efektivitas Konsultasi Dan Kolaborasi Di SMP Yayasan Islam Kota Tasikmalaya - Herwina Aprila; Feida Noorlaila Isti’adah; Salis Iklima; Isma Nurul Barokah; Lusi Susanti; Nazwa Ramadhani; Lutfi Raihan (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted with the aim of finding out the importance of consultation and collaboration in a school setting as well as increasing consultation and collaboration in the school environment to support students in solving problems or developing the students' potential. The methods used in collecting data are observation, interviews, literature and documentation. The results obtained from this research are the importance of the role of consultation and collaboration in increasing the role of students in society and themselves. In collaboration and consultation in schools, various parties are involved, such as subject teachers, homeroom teachers, parents, school principals and friends. peers are also guidance and counseling teachers. It is important that collaboration and consultation in schools involve cooperation and active participation by involving various parties. Consultation and collaboration can create a learning environment that is inclusive, supportive, and focuses on the quality of education.